Volatile and non-volatile/semi-volatile compounds and in vitro bioactive properties of Chilean Ulmo (Eucryphia cordifolia Cav.) honey. (April 2017) - Acevedo, Francisca; Torres, Paulina; Oomah, B. Dave; de Alencar, Severino Matias; Massarioli, Adna Prado; Martín-Venegas, Raquel; Albarral-Ávila, Vicenta; Burgos-Díaz, César; Ferrer, Ruth; Rubilar, Mónica
Abstract: Ulmo honey originating from Eucryphia cordifolia tree, known locally in the Araucania region as the Ulmo tree is a natural product with valuable nutritional and medicinal qualities. It has been used in the Mapuche culture to treat infections. This study aimed to identify the volatile and non-volatile/semi-volatile compounds of Ulmo honey and elucidate its in vitro biological properties by evaluating its antioxidant, antibacterial, antiproliferative and hemolytic properties and cytotoxicity in Caco-2 cells. Headspace volatiles of Ulmo honey were isolated by solid-phase microextraction (SPME); non-volatiles/semi-volatiles were obtained by removing all saccharides with acidified water and the compounds were identified by GC/MS analysis. Ulmo honey volatiles consisted of 50 compounds predominated by 20 flavor components. Two of the volatile compounds, lyrame and anethol have never been reported before as honey compounds. The non-volatile/semi-volatile components of Ulmo honey comprised 27 compounds including 13 benzene derivatives accounting 75% of the total peak area. Ulmo honey exhibited weak antioxidant activity but strong antibacterial activity particularly against gram-negative bacteria and methicillin-resistant Staphylococcus aureus (MRSA), the main strain involved in wounds and skin infections. At concentrations > 0.5%, Ulmo honey reduced Caco-2 cell viability, released lactate dehydrogenase (LDH) and increased reactive oxygen species (ROS) production in a dose dependent manner in the presence of foetal bovine serum (FBS). The wide array of volatile and non-volatile/semi-volatile constituents of Ulmo honey rich in benzene derivatives may partly account for its strong antibacterial and antiproliferative properties important for its therapeutic use. Our results indicate that Ulmo honey can potentially inhibit cancer growth at least partly by modulating oxidative stress. Graphical abstract: Highlights: Volatile and non-volatile/semivolatile compounds of Ulmo honey were identified by GC–MS. Two of the volatile compounds have never been reported before as honey compounds. Ulmo honey exibited weak antioxidant activity and strong antibacterial activity. Ulmo honey can inhibit cancer growth at least partly by modulating oxidative stress.